2018
DOI: 10.1038/s41477-017-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of auxin-induced callus formation by bZIP59–LBD complex in Arabidopsis regeneration

Abstract: Induction of pluripotent cells termed callus by auxin represents a typical cell fate change required for plant in vitro regeneration; however, the molecular control of auxin-induced callus formation is largely elusive. We previously identified four Arabidopsis auxin-inducible Lateral Organ Boundaries Domain (LBD) transcription factors that govern callus formation. Here, we report that Arabidopsis basic region/leucine zipper motif 59 (AtbZIP59) transcription factor forms complexes with LBDs to direct auxin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 47 publications
0
80
0
Order By: Relevance
“…The homo- and heterodimerization of LBD proteins are thought to be an important determinant of LR formation [29, 30]. The AtbZIP59 transcription factor has been reported to form complexes with LBDs to direct auxin-induced callus formation and LR development [31]. All these results suggest that homodimerization and heterodimerization of signaling components are important in LR formation.…”
Section: Discussionmentioning
confidence: 99%
“…The homo- and heterodimerization of LBD proteins are thought to be an important determinant of LR formation [29, 30]. The AtbZIP59 transcription factor has been reported to form complexes with LBDs to direct auxin-induced callus formation and LR development [31]. All these results suggest that homodimerization and heterodimerization of signaling components are important in LR formation.…”
Section: Discussionmentioning
confidence: 99%
“…MdLBD3, a gene homologous to AtLBD3/AtLBD9, is induced by exogenous cytokinin [38]. In rice (Oryza sativa L.), OsLBD3-1 is expressed only in roots, and OsLBD3-2 is expressed in roots, shoots, and petioles [39]. We found that a deletion on MdLBD3 promoter produced an additional MdWRKY2 binding motif and created a rise in MdLBD3 expression.…”
Section: Discussionmentioning
confidence: 81%
“…In Triticum aestivum, regeneration e ciency was associated with auxin exposure time and catalase metabolism during somatic embryogenesis. Induction of pluripotent cells, termed, "callus," by auxin represents a typical cell fate change required for plant in vitro regeneration [84]. Studies have shown that relative signaling through MONOPTEROS (MP)/ARF 5 was required for shoot formation in Arabidopsis callus.…”
Section: Discussionmentioning
confidence: 99%